A Cross-Correlation Analysis of Irradiation, Temperature and Wind Speed Based on Detrended Cross-Correlation Method - Xiaosheng WU; Yuewen JIANG (Zhongguo dianli)
Exploiting the interconnections among meteorological factors properly can reduce the operating costs and enhance the stability of the system. In this paper, the measured data of irradiation, wind velocity and temperature at three different areas in the United States are used to explore the long-range auto correlation and the interactions between these factors. First of all, the detrended fluctuation analysis method (DFA) is adopted to analyze the long-range auto correlation of these meteorological factors at three areas, respectively. Moreover, the detrended cross-correlation analysis method (DCCA) and the coefficient for reciprocity of DCCA is used to quantify the interactions of these three factors at different scales. Finally, several wind-solar hybrid generation scenarios are developed to evaluate the general and seasonal characteristics of the complementarity between wind and solar energy. The results verify the validity and necessity of the proposed model.